Genetic and non-genetic parameters of Kleiber ratio in Pantja goat under field conditions of Tarai region of Uttarakhand - KHADDA, B S; SINGH, BRIJESH; SINGH, D V; SINGH, S K; SINGH, C B; SINGH, J L (The Indian Journal of Animal Sciences, 2018)
A study was conducted to estimate the Kleiber ratio of 805 Pantja kids of 514 goats sired by 26 bucks maintained by registered farmers under All India Co-ordinated Research Project on Goats (Pantja field unit) during 2015–16. The overall least-squares mean and their standard error for Kleiber ratio at 0–3, 3–6, 6–9 and 9–12 months of age were 15.29±0.16, 5.50±0.15, 4.24±0.09 and 3.53±0.37 g respectively. The random effect of sire had a highly significant effect on KR1 (0–3 months) and KR2 (3–6 months) whereas, the effect was significant on KR3 (6–9 months) and KR4 (9–12 months). The heritability estimate for Kleiber ratio was 0.28±0.09, 0.27±0.09, 0.22±0.08 and 0.04±0.03 at 0–3, 3–6, 6–9 and 9–12 months of age respectively. Most of the genetic and phenotypic correlations of Kleiber ratio were negative between different periods. It may be concluded that the pre-weaning Kleiber ratio was higher which indicated that the kids were given full care during this period. The post-weaning Kleiber ratio can be improved through better management of kids after weaning.